Cloning and Identification of a Complete cDNA Coding for a Bactericidal and Antitumoral Acidic Phospholipase A(2) from Bothrops jararacussu Venom - Roberto, Patricia G.; Kashima, Simone; Marcussi, Silvana; Pereira, Jose O.; Astolfi-Filho, Spartaco; Nomizo, Auro; Giglio, Jose R.; Fontes, Marcos R. M. [UNESP]; Soares, Andreimar M.; Franca, Suzelei C. (Springer, 2004)
In order to better understand the function of acidic phospholipases A(2) (PLA(2)s) from snake venoms, expressed sequence tags (ESTs) that code for acidic PLA(2)s were isolated from a cDNA library prepared from the poly(A) + RNA of venomous glands of Bothrops jararacussu. The complete nucleotide sequence (366 bp), named BOJU-III, encodes the BthA-I-PLA(2) precursor, which includes a signal peptide and the mature protein with 16 and 122 amino acid residues, respectively. Multiple comparison of both the nucleotide and respective deduced amino acid sequence with EST and protein sequences from databases revealed that the full-length cDNA identified (BOJU III - AY145836) is related to an acidic PLA(2) sharing similarity, within the range 55-81%, with acidic phospholipases from snake venoms. Moreover, phylogenetic analysis of amino acid sequences of acidic PLA(2)s from several pit viper genera showed close evolutionary relationships among acidic PLA(2)s from Bothrops, Crotalus, and Trimeresurus. The molecular modeling showed structural similarity with other dimeric class II PLA(2)s from snake venoms. The native protein BthA-I-PLA(2), a nontoxic acidic PLA(2) directly isolated from Bothrops jararacussu snake venom, was purified and submitted to various bioassays. BthA-I-PLA(2) displayed high catalytic activity and induced Ca(2+)-dependent liposome disruption. Edema induced by this PLA(2) was inhibited by indomethacin and dexamethasone, thus suggesting involvement of the cyclo-oxygenase pathway. BthA-I-PLA(2) showed anticoagulant activity upon human plasma and inhibited phospholipid-dependent platelet aggregation induced by collagen or ADP. In addition, it displayed bactericidal activity against Escherichia coli and Staphylococcus aureus and antitumoral effect upon breast adrenocarcinoma as well as upon human leukemia T and Erlich ascitic tumor. Following chemical modification with p-bromophenacyl bromide, total loss of the enzymatic and pharmacological activities were observed. This is the first report on the isolation and identification of a cDNA encoding a complete acidic PLA(2) from Bothrops venom, exhibiting bactericidal and antitumoral effects.
Keywords: Acidic phospholipases A(2); antitumoral effect; bactericidal; Bothrops jararacussu; BPB-chemical modification; cDNA; structural analysis